Analysis of Nociceptive Information Encoded in the Temporal Discharge Patterns of Cutaneous C-Fibers - Cho, Kyeongwon; Jang, Jun Ho; Kim, Sung-Phil; Lee, Sang Hoon; Chung, Soon-Cheol; Kim, In Young; Jang, Dong Pyo; Jung, Sung Jun (Frontiers in Computational Neuroscience, 2016)
The generation of pain signals from primary afferent neurons is explained by a labeled-line code. However, this notion cannot apply in a simple way to cutaneous C-fibers, which carry signals from a variety of receptors that respond to various stimuli including agonist chemicals. To represent the discharge patterns of C-fibers according to different agonist chemicals, we have developed a quantitative approach using three consecutive spikes. By using this method, the generation of pain in response to chemical stimuli is shown to be dependent on the temporal aspect of the spike trains. Furthermore, under pathological conditions, gamma-aminobutyric acid resulted in pain behavior without change of spike number but with an altered discharge pattern. Our results suggest that information about the agonist chemicals may be encoded in specific temporal patterns of signals in C-fibers, and nociceptive sensation may be influenced by the extent of temporal summation originating from the temporal patterns.